Jobless Growth di Indonesia: Analisis Pengaruh Kesempatan Kerja, Pembiayaan Modal Kerja Syariah, Pendidikan dan Perkembangan Teknologi terhadap Tingkat Pengangguran di Indonesia - Saddam H. Leondi; Ady Cahyadi (Tauhidinomics: Journal of Islamic Banking and Economics, 2026)
The phenomenon of jobless growth in Indonesia indicates that economic growth and the expansion of employment opportunities have not been fully accompanied by a reduction in the unemployment rate. This study aims to analyze the effects of the employment rate, Islamic working capital financing, education—proxied by the average years of schooling—and technological development on the open unemployment rate in Indonesia. This research employs a quantitative approach using time-series data and the Autoregressive Distributed Lag (ARDL) method. The results show that all variables are jointly significant; however, partially, most variables do not exhibit significant effects in the long run. These findings confirm the presence of structural jobless growth and highlight the importance of labor policies that emphasize job quality and the alignment of workforce skills with market demands.